A secondary source configuration for control of a ventilation fan noise in ducts - Prezelj, Jurij (Strojniški vestnik, 2011)
The main noise source in heating, ventilation, and air conditioning systems is usually a ventilating fan. Noise, generated by the ventilating fan is transmitted through the duct into the living and working environment. A typical fan noise spectrum consists of a broadband noise, which is superimposed with pure tones. Different methods are available to reduce a transmission of such noise from the ventilating fan into the living and working environment. In this article it is demonstrated how a feedforward active noise control system can be implemented together with a side branch resonator. Effectiveness of the feedforward active noise control system depends on the quality of a reference signal, which should be in a perfect correlation with the primary noise. An acoustic feedback is the main problem of feedforward active noise control systems in ducts. A combined method uses asingle loudspeaker to work as a dipole source and a side branch resonator to reduce the acoustic feedback. A side branch resonator reduces noise transmission in a narrowband frequency range as well. In this article, a theoretical background of a dipole source with a side branch resonator is presented, along with some measurement results and simulations of active noise control.
Keywords: active noise control; aktivno dušenje hrupa; eng; fan; hrup; prezračevalni kanali; secondary source; sekundarni zračni vir; ventilation duct; ventilatorji